Paddington 2 [videorecording (DVD)] - King, Paul, 1978-; King, Paul, 1978-; Hawkins, Sally, 1976-; Bonneville, Hugh (Warner Bros. Entertainment, 2018)
When a book Paddington wants to buy is stolen, he sets out to find the thief and retrieve the book.